Effect of viscoelastic and surface properties on tack, peel adhesion and shear strength of polymer blends applied as hot melt pressure sensitive adhesive models comprising tackifying agents of various chemical nature - T. Abboud; A. Wutzler; H-J. Radusch (eXPRESS Polymer Letters)
Viscoelastic and surface properties of polymer blends prepared as models of hot melt pressure sensitive adhesives (HMPSA) were investigated and the correlation to tack, peel, and shear adhesion properties was discussed. Three different types of tackifiers, which present a softening point of ca. 100 °C as well as different compatibility degree with the midblock and the end-block of poly(styrene-block-isoprene-block-styrene) (SIS), were employed. A good association degree between the midblock and the tackifiers was observed. Surface energy was used to evaluate the blend compatibility trend. The blends presented lower surface energy than the pure materials due to non-polar and acid-base interactions. This is a feature of compatible blends. PSA character was observed based on the obtained results of tack and peel for the blends and it is a consequence of the adequate degree of compatibility of the tackifiers and the midblock. The compatibility of the tackifiers and the end-block influenced shear adhesion. Rosin ester resin showed a better association with the styrenic domains. The second maximum of the loss modulus (G″) curve for a blend containing rosin resin shifted to lower temperatures in comparison to blends containing the other investigated resins. The lowest holding power values were measured for the blends containing rosin ester resin. The styrene domains were pronouncedly disturbed by this resin.